Synthetic efforts toward lagunamide C: route development and implementation upon a model system - Hanks, Chelsea (Kansas State University, 2017)
The lagunamides are group of natural products derived from cyanobacterium. Lagunamides A, B, and C have shown impressive cytoxicity towards a panel of cancer and malarial cell lines. Each of the lagunamide family members share structural similarities within their polypeptide backbone, but the polyketide units with A/B differ from C by an additional methylene insertion. The total synthesis of lagunamide A and an analog of lagunamide B have been reported by Dai and Pal’s groups, respectively. The synthesis of lagunamide A was completed first by Dai and proved that the original structural elucidation was incorrect. With this inaccurate stereochemical assignment, it was suspected that this inaccuracy also appeared in the structural elucidation of Lagunamide B that was completed by Pal. It is alleged that these inaccuracies have occurred in the stereochemical assignments of the isolated structure of lagunamide C. In addition to the stereochemical inaccuracies, a new synthetic route is necessary to synthesize lagunamide C. The structures of lagunamides A and C are nearly identical, except for the addition of one carbon in the polyketide portion of lagunamide C. This additional carbon disallows the use of same synthetic methods applied on lagunamide A to be employed on the synthesis of the polyketide portion of lagunamide C. This work will discuss a modular approach towards the synthesis of lagunamide C. Model systems were employed to test the validity and success of the proposed route. Key steps of the proposed synthetic route include a titanium mediated mixed aldol reaction, cyclopropanation, and Charette cyclopropane ring-opening. The current synthetic route is shown to be scalable and possessing optimizable transformations. These steps have proven to be successful with the model systems and have laid the groundwork for the synthesis of the target compound, lagunamide C.
Keywords: Lagunamide C; Total synthesis